Numerical simulation of electromagnetic waves in Schwarzschild space–time by finite difference time domain method and Green function method - Jia, Shouqing; La, Dongsheng; Ma, Xuelian (Computer physics communications, 2018)
The finite difference time domain (FDTD) algorithm and Green function algorithm are implemented into the numerical simulation of electromagnetic waves in Schwarzschild space–time. FDTD method in curved space–time is developed by filling the flat space–time with an equivalent medium. Green function in curved space–time is obtained by solving transport equations. Simulation results validate both the FDTD code and Green function code. The methods developed in this paper offer a tool to solve electromagnetic scattering problems. Program Title: FDTD and Green function in Schwarzschild space–time Program Files doi:http://dx.doi.org/10.17632/8fxbp578ys.1 Licensing provisions: GPLv3 Programming language: MATLAB Nature of problem: Simulating electromagnetic waves in Schwarzschild space–time. Solution method: FDTD method and Green function method.